"MALDI-CSI": A proposed method for the tandem detection of human blood and DNA typing from enhanced fingermarks. (June 2021) - Kennedy, Katie; Bengiat, Ravell; Heaton, Cameron; Herman, Yael; Oz, Carla; Elad, Michal Levin; Cole, Laura; Francese, Simona
Highlights: MALDI MSP/I can detect and map blood in enhanced marks over paint. The application of MALDI MSP/I does not prevent subsequent DNA typing. An alternative forensic workflow for suspected blood marks on painted walls integrating MALDI MSP/I is suggested. MALDI MSP can detect blood in fingermarks concealed under a coat of paint. Graphical Abstract: ga1 Abstract: Matrix Assisted Laser Desorption Ionization Mass Spectrometry Profiling and Imaging (MALDI MSP and MALDI MSI), in combination with bottom up proteomics, have proven to successfully detect and map blood-derived peptide signatures in blood fingermarks, with high specificity and compatibility with a number of blood enhancement techniques (BET). In the present study, the application of MALDI MSP and MSI to blood marks has been investigated further. In particular, the MALDI based detection and visualisation of blood has been explored in tandem with DNA typing. This investigation has been undertaken in a scenario simulating blood fingermarks on painted walls. In the present study, two sets of marks were analysed with each set comprising of a depletion series of four marks deposited on a surface treated to simulate painted walls: Set I - developed with Ninhydrin (NIN) and Set II- developed with Acid Black-1 (AB-1). For both sets, the application of MALDI MSP was successful in detecting haem and human specific haemoglobin peptide markers. MALDI MSI also provided molecular images by visualising haem on the ridge pattern enhanced by BET. The feasibility of successful and subsequent DNA profiling from the recovered fingermarks was also assessed for marks that had undergone enzymatic in situ digestion and MALDI MSI; it was observed that in 73% of the samples analysed, a DNA profile suitable for comparison was obtained. Based on these results, a possible operational workflow has been proposed incorporating the use of a MALDI MS based approach as a confirmatory test for human blood enabling subsequent DNA typing.